Determination of Time, Space and Financial Parameters of the Model of Organization of Calendar Plan of Jizak Car Plant Construction, Analysis and Resource of Results - Begaliev Jasurbek Murodqosim O’g’li; Yusupov X.I. (Genius Journals, 2022)
Organizing the construction of the car plant in the flow method of calendar plan modeling, creating a methodology for developing a calendar plan, identifying technical and economic advantages and applying them in design practice.
Keywords: Construction of machine-building facilities; project model; communal; modern